The Regulation of Fuel Metabolism and Substrate Availability During the Prolonged Fast of the Northern Elephant Seal - Viscarra, Jose Abraham (eScholarship, University of California, 2013)
Food deprivation in mammals results in profound changes in fuel metabolism and substrate regulation. Among these changes are decreased reliance on the counter-regulatory dynamics by insulin-glucagon due to reduced glucose utilization, and increased concentrations of lipid substrates in plasma to meet the energetic demands of peripheral tissues. Prolonged food deprivation also increases lipid oxidation and utilization, which may contribute to the onset of the insulin resistance associated with fasting. Because insulin resistance promotes the preservation of glucose and oxidation of fat, it has been suggested to be an adaptive response to food deprivation. As the primary storage site of lipid substrates, adipose serves as a primary contributor to the regulation of metabolism in food deprived states. Through its regulation of lipolysis, adipose influences the availability of carbohydrate, lipid, and protein, and so, may potentially be a key regulator of fasting metabolism.The northern elephant seal pup (Mirounga angustirostris) naturally undergoes a 2-3 month post-weaning fast during which it depends primarily on the oxidation of fatty acids to meet its energetic demands. The concentration of non-esterified fatty acids (NEFA) increases and is associated with the development of insulin resistance-like symptoms in late-fasted pups. Additionally, plasma NEFA concentrations respond differentially to an intravenous glucose tolerance test (ivGTT) depending on fasting duration suggesting that impaired insulin action may play a key role in the regulation of metabolic substrates in prolong-fasted animals. However, because fasting mammals also exhibit hypoinsulinemia, the insulin resistance-like conditions they experience may actually result from reduced pancreatic sensitivity/capacity, necessitating further assessment to better understand these dynamic responses.We have previously reported that adipose Glut4 expression and AMP kinase (AMPK) activity increase and plasma glucose decreases in fasting seals suggesting that AMPK activity contributes to the regulation of metabolism via Glut4 during insulin resistance-like conditions in late fasted pups. Therefore the goals of this study were: (1) to assess the impact of fasting on the regulation of metabolic substrates and thereby identify the mechanisms that allow fasting-adapted mammals to tolerate prolonged food deprivation, and (2) to assess the insulin sensitivity status of fasting elephant seals pups to determine whether fasting results in insulin resistance or pancreatic dysfunction.To accomplish this we infused early- and late-fasted seals with either glucose (0.05 g/kg) or insulin (0.065 U/kg), and a separate group of late-fasted seals with low (10 pM/kg) or high (100 pM/kg) dosages of glucagon-like peptide-1 (GLP-1) immediately following a glucose bolus (0.5g/kg), and measured the systemic and cellular responses. Because GLP-1 facilitates the glucose-stimulated insulin secretion, these infusions provide a method to assess pancreatic capacity and responsiveness. Adipose tissue and plasma samples collected prior to the infusions were used to determine the effects of fasting duration. Samples collected during the infusions were used to assess insulin sensitivity and pancreatic function.Fasting was associated with an increased NEFA:glycerol ratio in plasma and an increased DAG:TAG ratio in adipose. Furthermore, fasting decreased the expressions of fatty acid transporters and hormone sensitive lipase, and increased the expression of adipose triglyceride lipase. This suggests that increased plasma NEFA results from: (1) decreased tissue NEFA uptake, and (2) the transition to partial hydrolysis. Insulin infusions increased the phosphorylation of insulin receptor and Akt in adipose and muscle; however the timing of the signaling response was blunted in adipose. Despite the dose-dependent increases in insulin and increased glucose clearance (high dose), both GLP-1 dosages produced increases in plasma cortisol and glucagon, and may have contributed to the glucogenic role of GLP-1.Results suggest that long-term fasting induces shifts in the regulation of lipolysis and lipid metabolism that contribute to the onset of insulin resistance in adipose, all-the-while maintaining insulin sensitivity in muscle. Furthermore, fasting does not impair pancreatic capacity, but does lead to decreased glucose tolerance. Impaired glucose tolerance may facilitate the onset of a whole-body insulin resistance-like condition despite the maintenance of skeletal muscle insulin sensitivity that serves to promote the preservation of metabolic substrates, especially glucose, while allowing for the continued development of fasting elephant seal pups.